Pharmacist independent prescribing in critical care: results of a national questionnaire to establish the 2014 UK position. (30th September 2015) - Bourne, Richard S.; Whiting, Paul; Brown, Lisa S.; Borthwick, Mark
Abstract: Objectives: Clinical pharmacist practice is well established in the safe and effective use of medicines in the critically ill patient. In the UK, independent pharmacist prescribers are generally recognised as a valuable and desirable resource. However, currently, there are only anecdotal reports of pharmacist‐independent prescribing in critical care. The aim of this questionnaire was to determine the current and proposed future independent prescribing practice of UK clinical pharmacists working in adult critical care. Methods: The questionnaire was distributed electronically to UK Clinical Pharmacy Association members (closed August 2014). Key findings: There were 134 responses to the questionnaire (response rate at least 33%). Over a third of critical care pharmacists were practising independent prescribers in the specialty, and 70% intended to be prescribers within the next 3 years. Pharmacists with ≥5 years critical care experience ( P < 0.001) or worked in a team ( P = 0.005) were more likely to be practising independent prescribers. Pharmacists reported significant positives to the use of independent prescribing in critical care both in patient care and job satisfaction. Independently, prescribing was routine in: dose adjustment for multi‐organ failure, change in route or formulation, correction prescribing errors, therapeutic drug monitoring and chronic medication. The majority of pharmacist prescribers reported they spent ≤5% of their clinical time prescribing and accounted for ≤5% of new prescriptions in critical care patients. Conclusions: Most critical care pharmacists intend to be practising as independent prescribers within the next 3 years. The extent and scope of critical care pharmacist prescribing appear to be of relatively low volume and within niche prescribing areas.